Mineral and organic fertilizing on the melon crop in a Vertisol of the Submiddle São Francisco Valley, Brazil - de Faria, Clementino M. B.; Pereira, José Ribarmar; Possídeo, Edson L. (Pesquisa Agropecuaria Brasileira, 1994)
This work was composed of two experiments with melon (Cucumis melo L.), carried out in 1989 and 1990 in two places in a Vertisol in Juazeiro, BA, Brazil. The treatments consisted of levels of nitrogen, phosphorus, potassium, and cattle manure. The results showed that melon responded positively to nitrogen, phosphorus and potassium fertilization, but not to cattle manure in both experiments. In one experiment, it was possible to determine the economical levels for the three nutrients, which were: 74 kg/ha of N, 114 kg/ha of P2O5 and 156 kg/ha of K2O, giving an average yield of 30,425 kg/ha. The N had a positive influence on the brix and on the number of fruits. The P influenced positively the weight of fruits.